Comparison of the Adomian Decomposition Method and Regular Perturbation Method on Nonlinear Equations Second Kind of Volterra (European Journal of Pure and Applied Mathematics, 2021)
In this paper, we study convergence of Adomian decomposition method applied tosecond kind Volterra general integral and show that this method and regular perturbation method converges to the same solution.
Keywords: Adomian Decomposition Method (ADM); Regular Pertuba- tion Method(RPM); Volterra integral equation second kind.